Optimal conditions for lentiviral transduction of engrafting human CD34(+) cells - Uchida, N (Gene Ther, 2011)
Cytokines are required for γ-retroviral transduction of human CD34(+) cells. However, cytokines may reduce engraftment of CD34(+) cells and may not be necessary for their lentiviral transduction. We sought to optimize transduction and engraftment of human CD34(+) cells using lentiviral vectors. Single 24 h transduction of human CD34(+) cells with human immunodeficiency virus type 1 (HIV1)-based lentiviral vectors in media containing stem cell factor (SCF), FMS-like tyrosine kinase 3 (FLT3) ligand, thrombopoietin (each 100 ng ml(−1)) and 10% fetal bovine serum was compared with various cytokine conditions during ex vivo culture and assayed using humanized xenograft mice for 6 months after transplantation. Serum-free media improved transduction efficiency of human CD34(+) cells. Interleukin-3 (20 ng ml(−1)) had little effect on transduction efficiency or engraftment. Threefold higher cytokine mixture (each 300 ng ml(−1)) reduced engraftment of CD34(+) cells. SCF alone (100 ng ml(−1)) proved insufficient for maintaining engraftment ability and reduced transduction efficiency. Short-term prestimulation had little effect on transduction efficiency or engraftment, yet 24 h prestimulation showed higher transduction efficiency, higher gene expression levels and lower engraftment. In summary, 24 h prestimulation followed by single 24-h lentiviral transduction in serum-free media with SCF, FLT3 ligand and thrombopoietin yields high transduction efficiency to engrafting human CD34(+) cells, and is applicable in human clinical gene therapy trials.